How Risky is Risk Management: Case Study of Bupa Arabia - Azid, Tosef; Burki, Umar (IIUM Journal of Case Studies in Management, 2021)
â€œWelcome to our CSR (Corporate Social Responsibility) section, said Loay Hisham Nazer, Chairman of the Bupa Arabia. CSR is a relatively new business term and something that has only become prevalent in the global business world recently. However, in Bupa Arabia, we have always believed in our duty as part of the larger community and have been active from the day we started. Itâ€™s something weâ€™ve strongly believed in and actively applied to what we do; we just hadnâ€™t put a â€˜CSRâ€™ label to it yet.â€ â€œWe aim to make a real and positive impact on the health of our community, starting from our employees and finally reaching out to communities for protecting them from the risk. Since our ambition was high, we had to rely on our best knowledge and professional skills to change our peopleâ€™s lives significantly. Providing our core competency (health insurance) to those who need it the most gives us strong belief and confidence to add genuine value and uplift their health conditions to their best shapes. Our actions speak louder than our words, and you can find more details about our programs in this section, which I hope you enjoyâ€, concluded the chairman, Loay Hisham Nazer. The CEO of Bupa Arabia, Tal Nazer, expressed his happiness and said, â€œBupa Arabia is a leading entrepreneurial enterprise in the field of women’s empowerment. We employ them to support our national economy and investment in human resources. Our leadership provides innovative services, which makes Bupa Arabia the first choice for companies that care about the health of their employees in all parts of the Kingdom of Saudi Arabia.â€ Mr. Arif Hunashi, Chief Operating Officer at Bupa Arabia, said, â€œWe, at Bupa, always strive to provide the best healthcare for you and your family. We do not limit ourselves to merely providing the best high-quality health insurance services, but we go beyond. Weâ€™re seeking to provide you with holistic healthcare in your daily lives.â€